Connexin 43 Hemichannels Regulate Osteoblast to Osteocyte Differentiation - Hua, Rui; Gu, Sumin; Jiang, Jean X. (Frontiers in Cell and Developmental Biology, 2022)
Connexin 43 (Cx43) is the predominant connexin subtype expressed in osteocytes. Osteocytes, accounting for 90%-95% of total bone cells, function as orchestrators coordinating balanced activity between bone resorbing osteoclasts and bone forming osteoblasts. In this study, two newly developed osteocytic cell lines, OCY454 and IDG-SW3, were used to determine the role of Cx43 gap junctions and hemichannels (HCs) in the regulation of osteoblast to osteocyte differentiation. We found that Cx43 level was substantially increased during the differentiation of IDG-SW3 cells, and is also much higher than that of OCY454 cells. We knocked down (KD) Cx43 expression using lentiviral CRISPR/Cas9 approach and inhibition of Cx43 HCs using Cx43(E2) antibody in IDG-SW3 cells. Cx43 KD or Cx43 HC inhibition decreased gene expression for osteoblast and osteocyte markers, including alkaline phosphatase, type I collagen, dentin matrix protein 1, sclerostin, and fibroblast growth factor 23, whereas increasing osteoclastogenesis indicator, receptor activator of nuclear factor kappa-B ligand (RANKL)/osteoprotegerin (OPG) ratio at early and late differentiation stages. Moreover, mineralization was remarkably attenuated in differentiated Cx43 deficient IDG-SW3 cells compared to ROSA26 control. Conditioned medium collected from fully differentiated IDG-SW3 cells with Cx43 KD promoted osteoclastogenesis of RAW264.7 osteoclast precursors. Our results demonstrated that Cx43 HCs play critical roles in osteoblast to osteocyte differentiation process and regulate osteoclast differentiation via secreted factors.